2015
DOI: 10.1007/s00418-015-1341-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aquaporin expression in liver with a focus on hepatocytes

Abstract: A deeper understanding of aquaporins (AQPs) expression and transcriptional regulation will provide useful information for liver pathophysiology. We established a complete AQPs mRNA expression profile in human and mouse liver, as well as protein localization of expressed AQPs. Additionally, the modulation of AQPs mRNA levels in response to various agents was determined in human HuH7 cells and in primary culture of mouse hepatocytes. AQP1, AQP3, AQP7, AQP8, and AQP9 mRNA and protein expressions were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 108 publications
3
38
0
2
Order By: Relevance
“…The involvement of AQPs in the liver must also be considered on the basis of their identification and different distribution in several hepatic cell types, as recently demonstrated [22,41]. The cited authors have charted in the human liver and in both human and mouse hepatocytes the presence of several AQPs providing interesting gene regulation by known drugs/hormones (i.e., dexamethasone, forskolin, rosiglitazone, and ghrelin).…”
Section: Liver Aqp Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…The involvement of AQPs in the liver must also be considered on the basis of their identification and different distribution in several hepatic cell types, as recently demonstrated [22,41]. The cited authors have charted in the human liver and in both human and mouse hepatocytes the presence of several AQPs providing interesting gene regulation by known drugs/hormones (i.e., dexamethasone, forskolin, rosiglitazone, and ghrelin).…”
Section: Liver Aqp Functionmentioning
confidence: 98%
“…In particular, the liver strongly expresses at least six AQPs (AQP1, 3, 7, 8, 9, and 11) [22,39,41,57]. Immunohistochemical studies revealed the expression of AQPs in different hepatic cell types, such as in cholangiocytes (AQP1 and AQP7), endothelial cells (AQP1), Kupffer cells (AQP3), and hepatocytes, (AQP7, 8, and 9) [22]. …”
Section: Aqp Structure and Distribution In Gutmentioning
confidence: 99%
“…AQP7 expression has also been documented in both human [18,67,84,85,86] and mouse [67,84,87] liver. However, others have reported no AQP7 expression in murine [3,14,15,82] and rat [6] liver, and studies of human AQP7 have indicated no [4] or very low levels of AQP7 mRNA in liver [85].…”
Section: Livermentioning
confidence: 99%
“…However, others have reported no AQP7 expression in murine [3,14,15,82] and rat [6] liver, and studies of human AQP7 have indicated no [4] or very low levels of AQP7 mRNA in liver [85]. In human liver, AQP7 has been localized to the cytoplasmic domain of hepatocytes [84,88] and the apical plasma membrane domain of cholangiocytes and endothelial cells [84]. In mice immunohistochemical staining was observed just in the hepatocyte cytoplasmic domain [84].…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation